Global well-posedness for the three-dimensional Navier–Stokes–Maxwell system with damping. (July 2023) - Liu, Hui; Sun, Chengfeng; Xin, Jie
Abstract: The three-dimensional Navier–Stokes–Maxwell system with damping is considered in this paper. Existence and uniqueness of strong solutions for the three-dimensional Navier–Stokes–Maxwell system with damping are proved for β ≥ 3 .